Análise da influência do lama nas canelas no Turismo de Arraias-TO - JESUS, Ana Kayla Silva de (Universidade Federal do Tocantins, 2025)
Tourism can be understood as activities related to transportation, accommodation, food, cultural activities, leisure and entertainment. And it has great transformative capacity, as it can completely change the economic structure of a place/city, resulting in better living conditions for local populations. The general objective of the work is to investigate the emergence of the Lama nas Canelas event and its relationship with tourism in the city of Arraias -TO. Specific objectives aim to: identify how adventure tourism can influence and move the hotel economy of Arraias; get to know the Lama nas canelas event; Understand what ecotourism is; verify adventure tourism practices in the city Arraias - TO. The general objective of the work is to investigate the emergence of the Lama Naps Canelas event and its relationship with tourism in the city of Arraias -TO. Specific objectives aim to: identify how adventure tourism can influence and move the hotel economy of Arraias; get to know the Lama Nas canelas event; Understand what ecotourism is; verify adventure tourism practices in the city Arraias -TO.